Lobbying, a atividade dos grupos de interesse e grupos de pressão: atuação e direito - Avizú, Cristiane (2007)
In this work we try to analyze the factor of the meeting of man in society and the organization of said society in a State, with the aim to establish the main reason of this meeting, the Common Good. Afterwards, we walk along the evolution of the constitutionalistic order, the factors that give us the power to enter the constitutionalistic thought, and promote the conjugation of the participation in the democratic process in an equal form, with the hypotheses of influence of the interest groups and press ion groups in the legislative elaboration when performing the Lobbying activity, including the contributions or damages arising out of this performance, as well as the normative aspects that characterize this actuation as it is or n the contrary, where we notice the principle of the basic isonomy, in order to preserve a participation in the Law preparation process, in equal conditions, without giving way to the economical power pressure and so we shall preserve the public interest and common good